The Lee Strasberg notes - Strasberg, Lee.; Cohen, Lola.; T&F eBooks (London ; New York : Routledge, 2010)
Never before published transcripts from Lee Strasberg's teachings at his school in New York City in the last ten years of his life.
Includes bibliographical references and index.
Also available in print edition.
Mode of access: World Wide Web.
Keywords: Strasberg, Lee; Method acting; Acting -- Study and teaching; Theater -- Production and direction; Electronic books